Mastering ABP Framework: Build maintainable .NET solutions by implementing software development best practices - Kalkan, Halil İbrahim (Packt Publishing, 2022)
Learn how to build modern web applications from the creator of ABP Framework Key Features Build robust, maintainable, modular, and scalable software solutions using ABP FrameworkLearn how to implement SOLID principles and domain-driven design in your web applicationsDiscover how ABP Framework speeds up your development cycle by automating repetitive tasks Book Description ABP Framework is a complete infrastructure for creating modern web applications by following software development best practices and conventions. With ABP's high-level framework and ecosystem, you can implement the Don’t Repeat Yourself (DRY) principle and focus on your business code. Written by the creator of ABP Framework, this book will help you to gain a complete understanding of the framework and modern web application development techniques. With step-by-step explanations of essential concepts and practical examples, you'll understand the requirements of a modern web solution and how ABP Framework makes it enjoyable to develop your own solutions. You'll discover the common requirements of enterprise web application development and explore the infrastructure provided by ABP. Throughout the book, you’ll get to grips with software development best practices for building maintainable and modular web solutions. By the end of this book, you'll be able to create a complete web solution that is easy to develop, maintain, and test. What you will learn Set up the development environment and get started with ABP FrameworkWork with Entity Framework Core and MongoDB to develop your data access layerUnderstand cross-cutting concerns and how ABP automates repetitive tasksGet to grips with implementing domain-driven design with ABP FrameworkBuild UI pages and components with ASP.NET Core MVC (Razor Pages) and BlazorWork with multi-tenancy to create modular web applicationsUnderstand modularity and create reusable application modulesWrite unit, integration, and UI tests using ABP Framework Who this book is for This book is for web developers who want to learn software architectures and best practices for building maintainable web-based solutions using Microsoft technologies and ABP Framework. Basic knowledge of C# and ASP.NET Core is necessary to get started with this book.